2018
DOI: 10.1007/s10107-018-1325-x
|View full text |Cite
|
Sign up to set email alerts
|

Fully dynamic bin packing revisited

Abstract: We consider the fully dynamic bin packing problem, where items arrive and depart in an online fashion and repacking of previously packed items is allowed. The goal is, of course, to minimize both the number of bins used as well as the amount of repacking. A recently introduced way of measuring the repacking costs at each timestep is the migration factor, defined as the total size of repacked items divided by the size of an arriving or departing item. Concerning the trade-off between number of bins and migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 45 publications
1
61
0
Order By: Relevance
“…In contrast, Feldkord et al [14] presented a simple robust 1 + ǫ-competitive algorithm with amortized migration factor that also works for the dynamic case. Berndt et al also showed that a worst-case migration factor of Ω(1/ǫ) is needed [5]. This lower bound was shown to also hold for amortized migration by Feldkord et al [14].…”
Section: Related Workmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, Feldkord et al [14] presented a simple robust 1 + ǫ-competitive algorithm with amortized migration factor that also works for the dynamic case. Berndt et al also showed that a worst-case migration factor of Ω(1/ǫ) is needed [5]. This lower bound was shown to also hold for amortized migration by Feldkord et al [14].…”
Section: Related Workmentioning
confidence: 93%
“…Jansen and Klein [17] designed new techniques in order to obtain a migration factor polynomial in 1/ǫ. These techniques were improved by Berndt et al [5] to also handle the dynamic version of the Bin Packing problem where items can also depart. In all of these works, the migration factor is worst-case and can thus not be saved up for later use.…”
Section: Related Workmentioning
confidence: 99%
“…The development of advanced LP/ILP-techniques made this notable improvement possible. Furthermore, in [4] Berndt, Jansen, and Klein built upon the techniques developed in [18] to give an AFPTAS for fully dynamic bin packing with a similar migration factor.…”
Section: Related Workmentioning
confidence: 99%
“…A general approach in the design of robust online algorithms is to rethink existing algorithmic strategies that work for the corresponding offline problem in a way that the algorithm can adapt to a changing problem instance. The experiences that were made so far in the design of robust algorithms (see [18,4,26]) are to design the algorithm in a way such that the generated solutions fulfill very tight structural properties. Such solutions can then be adapted more easily as new items arrive.…”
Section: Technical Contributionmentioning
confidence: 99%
See 1 more Smart Citation